At Westonci.ca, we provide reliable answers to your questions from a community of experts. Start exploring today! Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.

Given that the function g is defined by the rule g(x)=3-2x,determine the following

g(a)=


Sagot :

Answer:

The value of g(a) is:

  • g(a) = 3 - 2a

Step-by-step explanation:

Given

As the function g(x) is given by

[tex]g(x)=3-2x[/tex]

To determine

g(a) = ?

In order to determine g(a),

substitute x = a in the function g(x) = 3 - 2x

g(x) = 3 - 2x

g(a) = 3 - 2(a)

g(a) = 3 - 2a

Therefore, the value of g(a) is:

  • g(a) = 3 - 2a
We hope our answers were useful. Return anytime for more information and answers to any other questions you have. We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Get the answers you need at Westonci.ca. Stay informed with our latest expert advice.